The role of the medical social worker with patients with Complicated Grief disorder - Al-Anazi, Norah Farhan; Al-Hakami, Husain Mohammed (Journal of Humanities & Social Sciences, 2023)
The medical social worker plays an important role in dealing with psychological and social problems in the health and psychological sectors. One of the psychological disorders that social workers have a significant role is complicated grief disorder, which is one of the disorders that has been widely debated recently among researchers and practitioners in the field of mental health. In the year 2022, the revised version of the the Diagnostic and Statistical Manual of Mental Disorders was issued by the American Psychological Association, which concluded that it is considered a mental disorder and defined diagnostic criteria for its diagnosis, which removed it from the circle of disorders that need to be studied and separated from depression disorder.This study aimed to develop a theoretical conception of the important role that medical social workers play in helping patients who have been diagnosed with complicated grief disorder, by using the conceptualize approach through theoretical and analytical review of studies and research that dealt with the subject of the research. The results showed that the role of the medical social worker is an important and pivotal role in dealing with bereavement cases, whether before or after death. Social worker can provide a variety of professional interventions, such as advance care planning, psychological, emotional, and spiritual support, and help the patients organizing their life after the experience the loss of loved one.
Keywords: medical social worker; severe loss grief disorder; social problems; psychological disorders